Compensation, Spiritual Motivation, and Job Satisfaction: A Case Study of Sumsel Babel Sharia Bank - Muhammad Ichsan Hadjri; Badia Perizade; Zunaidah Zunaidah (Faculty of Economics, Universitas Sriwijaya, 2019)
This study aims to determine the effect of compensation and spiritual motivation on employee job satisfaction at Sumsel Babel Sharia Bank. The unit of analysis in this study were the employees at Sumsel Babel Sharia Bank with the population of 245 people. The population is employees at the Sumsel Babel Sharia Bank with permanent employee status. By using the Slovin formula and the stratified proportional random sampling method, 152 people were choosen as samples and respondents in this study. The results showed that compensation had a positive and significant effect on job satisfaction. In line with these results, spiritual motivation also had a positive and significant effect on job satisfaction. The results also indicates that compensation and spiritual motivation together had positive and significant effect on employee job satisfaction.